Pengaruh Pendidikan dan Pelatihan (Diklat) Terhadap Kinerja Pegawai di Dinas Kesehatan Kabupaten Sleman - Ninda Kirani Rizki; Erni Saharuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human resources play a central role in ensuring the sustainability and development of an organization. Therefore, the formation of qualified personnel cannot be ignored. Employee professionalism and discipline are necessary to provide optimal contributions to agency performance. This study aims to analyze the influence of education and training on employee performance at the Sleman Regency Health Office. This study uses a quantitative descriptive method with an associative approach. The research sample consisted of 62 respondents determined through purposive sampling technique. Data were collected through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The results showed that education and training had a significant effect on employee performance, with a t-value of 8.306 greater than the t-table of 2.000. The coefficient of determination (R²) of 0.535 indicates that 53.5% of employee performance variation is influenced by education and training, while the rest is determined by other factors. Thus, education and training play an important role in improving employee performance. Further research is recommended using method triangulation and adding variables such as motivation, organizational culture, and reward systems to obtain a more comprehensive picture of the determinants of ASN performance.